CO2 favours the accumulation of excess fluids in felsic magmas. (28th September 2020) - Pistone, Mattia; Caricchi, Luca; Ulmer, Peter
Abstract: Deformation and gas emissions at active volcanoes provide insights into volcanic plumbing systems. Large discrepancies are observed between the volumes calculated from deformation data and the volumes of erupted magmas and are ascribed to the amount of excess fluids in magma reservoirs, which hinders our capacity to predict the magnitude of an imminent eruption. Here, a series of experiments demonstrates that the amount of trapped excess fluids in felsic magmas depends strongly on fluid composition. Magmas with CO2 excess fluids become permeable at 44% larger porosities with respect to the H2 O‐rich counterparts at equivalent crystallinity. Available excess gas geochemistry and juvenile porosity data from felsic systems reveal that the volume discrepancy between erupted magma and syn‐eruptive SO2 increases with CO2 excess in magmas. These data highlight that CO2 ‐rich fluids enhance magma's capacity to store excess volatiles and shed light on the largest discrepancies between pre‐eruptive deformation and eruption intensity and magnitude.